2023
DOI: 10.1111/cns.14282
|View full text |Cite
|
Sign up to set email alerts
|

Paraventricular nucleus‐central amygdala oxytocinergic projection modulates pain‐related anxiety‐like behaviors in mice

Abstract: AimsAnxiety disorders associated with pain are a common health problem. However, the underlying mechanisms remain poorly understood. We aimed to investigate the role of paraventricular nucleus (PVN)‐central nucleus of the amygdala (CeA) oxytocinergic projections in anxiety‐like behaviors induced by inflammatory pain.MethodsAfter inflammatory pain induction by complete Freund's adjuvant (CFA), mice underwent elevated plus maze, light–dark transition test, and marble burying test to examine the anxiety‐like beha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 33 publications
0
6
0
Order By: Relevance
“…Intriguingly, HCN channels' inhibition had no effects on SNI‐induced anxiety‐like behaviors. We speculated that HCN channels in the LHb serve a crucial role in regulating depressive‐like behaviors, while anxiety‐like behaviors in SNI 6w mice might be associated with other neural mechanisms in the LHb or related to other brain regions, such as the amygdala, 56 , 57 , 58 , 59 hippocampus, 60 and prefrontal cortex. 61 , 62 Further investigations were required to confirm these speculations.…”
Section: Discussionmentioning
confidence: 99%
“…Intriguingly, HCN channels' inhibition had no effects on SNI‐induced anxiety‐like behaviors. We speculated that HCN channels in the LHb serve a crucial role in regulating depressive‐like behaviors, while anxiety‐like behaviors in SNI 6w mice might be associated with other neural mechanisms in the LHb or related to other brain regions, such as the amygdala, 56 , 57 , 58 , 59 hippocampus, 60 and prefrontal cortex. 61 , 62 Further investigations were required to confirm these speculations.…”
Section: Discussionmentioning
confidence: 99%
“…In human positron emission tomography (PET) studies, use of radioactive ligands has revealed alterations in the binding potential of μ-opioid receptors in chronic pain sufferers (e.g., Zubieta et al, 2001;Maarrawi et al, 2007;Li Y.-J. et al, 2023;.…”
Section: Opioidsmentioning
confidence: 99%
“…In animal studies, analgesic effects of oxytocin have been described after experimentally induced acute (Rash et al, 2014), neuropathic and inflammatory pain experiences (Yu et al, 2003;Condes-Lara et al, 2005;Eliava et al, 2016;Sun et al, 2018;Hilfiger et al, 2020;Li et al, 2021;Esmaeilou et al, 2022;Nishimura et al, 2022;Iwasaki et al, 2023;Krabichler and Reynders, 2023;Li Y.-J. et al, 2023;, and increased expression of oxytocin receptors has been reported after chemotherapy-induced neuropathic pain in mice (Li et al, 2023a).…”
Section: Oxytocinmentioning
confidence: 99%
See 1 more Smart Citation
“…The bursting pattern is regulated by various physiological and environmental factors, such as sensory stimuli, including touch, suckling, and sexual activity. These stimuli activate specific brain regions, leading to increased activity in oxytocin [22,30,31]…”
Section: Physiological Relevance (Bursting Behavior Etc)mentioning
confidence: 99%